2018
DOI: 10.1021/jacs.8b11477
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis Enables Structural Reengineering of Aglaroxin C Leading to Inhibition Bias for Hepatitis C Viral Infection

Abstract: As a unique rocaglate (flavagline) natural product, aglaroxin C displays intriguing biological activity by inhibiting HCV viral entry. To further elucidate structure-activity relationships and diversify the pyrimidinone scaffold, we report a concise synthesis of aglaroxin C utilizing a highly regioselective pyrimidinone condensation. We have prepared more than forty aglaroxin C analogues utilizing various amidine condensation partners. Through biological evaluation of analogues, we have discovered two lead com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 92 publications
0
31
0
Order By: Relevance
“…For immortalized or primary MEFs the medium was changed every day, for 7 or 12 days, for primary colon fibroblasts, half of the medium was changed for 3-5 days, after which the glass slides were removed from the plate carefully and imaged using SHG for collagen imaging. For HSF1 inhibition, CMLD011866 (aglaroxin C 40,41 ) was first optimized to determine the maximal dose at which cell viability is not compromised (500 nM). Based on this optimization, 3 nM CMLD011866 was added daily to primary WT colon fibroblasts for 3-5 days and SHG imaging was performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For immortalized or primary MEFs the medium was changed every day, for 7 or 12 days, for primary colon fibroblasts, half of the medium was changed for 3-5 days, after which the glass slides were removed from the plate carefully and imaged using SHG for collagen imaging. For HSF1 inhibition, CMLD011866 (aglaroxin C 40,41 ) was first optimized to determine the maximal dose at which cell viability is not compromised (500 nM). Based on this optimization, 3 nM CMLD011866 was added daily to primary WT colon fibroblasts for 3-5 days and SHG imaging was performed.…”
Section: Discussionmentioning
confidence: 99%
“…8a), suggesting that HSF1 does not play an essential role in contractility. To demonstrate that ECM deposition by colon fibroblasts is HSF1-dependent, we used the synthetic small molecule CMLD011866 ((-)-aglaroxin C [40][41][42] , Fig. 7g).…”
Section: Loss Of Hsf1 Attenuates Inflammation-induced Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These events are inhibited by several flavaglines, and in particular aglaroxin C (6), which displays a potency and therapeutic index superior to that of rocaglamide (1) and other flavaglines. Optimization of aglaroxin C led to the development of CMLD012043 (9) and CMLD012044 (10), which show an enhanced inhibition of HCV infection with low cytotoxicity [56]. These two compounds inhibit HCV viral entry into cells, but not HCV RNA replication and mRNA translation, suggesting that these effects are mediated by an action on PHBs rather than eIF4A.…”
Section: Antiviral Activitiesmentioning
confidence: 99%
“…1 ) were found to prevent the localization of PHBs at the cell surface, and consequently to block C-RAF activation and to reduce HCV infection with an EC 50 of 4 and 0.04 nM (incubation of 48 h in Huh7.5.1 cells) respectively. Thereafter Porco and collaborators synthesized aglaroxin C analogues and showed that two of them, CMLD012043 ( 8 ) and CMLD012044 ( 9 ), showed 3-fold greater inhibition of HCV infection in comparison to aglaroxin C and also with very low cytotoxicity [ 16 ].…”
Section: Antiviral Activities Of Flavaglines Mediated By Prohibitinsmentioning
confidence: 99%